Structural and tectonic development of the Indo-Burma ranges - C. K. Morley (2020)
© 2019 Elsevier B.V. The Indo-Burma Ranges form an enigmatic mountain belt, with fragments of evidence for an early accretionary history (Jurassic Jade belt HP-LT metamorphism; Early Cretaceous ophiolites; highly deformed Triassic turbidites (Pane Chaung Formation, PCF); Kanpetlet Schists). It remains uncertain whether this early history involved collision of a microcontinent (Mt. Victoria Land, MVL), unconformably sealed by Aptian-Cenomanian limestones, or can be explained entirely as an accretionary-type ophiolite on the western margin of the West Burma Terrane (WBT). Complex deformation in the deepwater Triassic, Jurassic, Late Cretaceous, and Paleogene deepwater sequences is replaced in the Late Eocene-Early Oligocene by molasse deposition. These events mark closure of the Neo-Tethys ocean between India and the IBR/WBT, and the onset of major dextral translation (>2000 km, 40 Ma-Recent), between the coupled India/IBR/WBT region and Sundaland. In the Late Miocene-Recent major transpressional deformation affected the IBR and Central Basin of the WBT. The late deformation events, sedimentary depocentres, and impinging thick crustal regions of the eastern Himalayas and Shillong Plateau, have all affected the overall shape (wedge taper) of the modern IBR, with the wedge and retro-wedge behaving anomalously compared with typical accretionary prisms. All tectonic models proposed for the IBR/WBT have weaknesses or ambiguities, and there is considerable scope for future research to resolve the many outstanding, tectonic, metamorphic, structural, and sedimentary issues. These are important tasks because the IBR is a key region for understanding the development of northern Gondwana, the Himalayan orogeny, and SE Asia, as well as providing insights into the complex development of highly oblique collisional margins.